Domestic violence: a study on the legal protection for women in Malaysia / Adilah Mohtar, Saidatun Nadiah Mohd Noh and Sarah Munirah Abdullah. - Mohtar, Adilah; Mohd Noh, Saidatun Nadiah; Abdullah, Sarah Munirah (2007)
Until recently, most walks in life in Malaysia regarded domestic violence as a taboo subject. Victims refuse to talk and prefer to suffer in silent while the abusers kept being inhumane, thinking that no law can stop them. Although these inhumane conducts are wrong, the laws do not seem to be serious enough in protecting the victims by not recognizing domestic violence as a specific crime. This research is conducted for the purpose of analyzing the current laws on domestic violence. In this research we will attempt to discuss the effectiveness, the weaknesses and the strength of Domestic Violence Act 1994, the Penal Code and Criminal Procedure Code which are inter-related with the offence of domestic violence. Furthermore, this research is conducted with the aim of educating the society so that they will recognize domestic violence as an act of crime. Thus, it is hoped that the society would be aware and understand the negative impact of domestic violence in the society if the effort set out to prevent it is insufficient. Besides that, we will also attempt to seek for remedies and solutions to the long standing problem faced by women in their homes, namely domestic violence.